11. KNOWLEDGE, ATTITUDES, PRACTICES AND SOME FACTORS ASSOCIATED WITH SOIL-TRANSMITTED HELMINTH INFECTIONS IN PRIMARY SCHOOL STUDENTS IN QUANG NINH PROVINCE IN 2021 (Vietnam Journal of Community Medicine, 2025)
The study was conducted on 420 primary students in Quang Ninh in 2021 to describe knowledge, attitudes, and practices of the students toward soil-transmitted helminthiasis prevention. Results showed that 40% of the students knew two types of helminths; 36.7% knew one type of helminth; 10.4% knew 3 types; and 12.9% of the students did not know any type of worm. Those students who were aware of one harmful effect of soil-transmitted helminthiasis accounted for 41.7%, 44.3% knew 2 or more harmful effects, and 14% did not know any harmful effects of soil-transmitted helminthiasis. The percentage of students with knowledge about one preventive measure, 2 or more prevenetive measures, and no preventive measures for soil-transmitted helminthiasis was 49.3%, 38.8%, and 11.9% respectively. Most of the students' families (97.1%) had hygienic latrines, and 100% of the students were dewormed. Students' personal hygiene practices for soil-transmitted helminthiasis included foot wearing (98.3%), not drinking unboiled water (96.7%), hand washing before eating (92.9%), hand washing after defecation (92.6%), and regular deworming (100%). There should be measures on health education and communication to enhance students' knowledge, attitudes, and practices on prevention of helminthic diseases, also deworming routines once or twice a year for primary school students.
Keywords: Knowledge; attitudes; practices; primary school students; soil-transmitted